2018
DOI: 10.1038/s41598-018-25551-0
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic impedance matched buffers enable separation of bacteria from blood cells at high cell concentrations

Abstract: Sepsis is a common and often deadly systemic response to an infection, usually caused by bacteria. The gold standard for finding the causing pathogen in a blood sample is blood culture, which may take hours to days. Shortening the time to diagnosis would significantly reduce mortality. To replace the time-consuming blood culture we are developing a method to directly separate bacteria from red and white blood cells to enable faster bacteria identification. The blood cells are moved from the sample flow into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 57 publications
(71 reference statements)
0
62
0
Order By: Relevance
“…Many label-free microfluidic methods for bacteremic blood sample preparation rely on direct size-based separation without prior lysis 26,27,45,[63][64][65][66][67][68][69] . Besides the reduction of blood cells of larger or similar diameter than the targeted bacteria and the potential release of phagocytosed but viable bacterial cells 38 , other benefits might arise from selective blood cell lysis as a first step in sample preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many label-free microfluidic methods for bacteremic blood sample preparation rely on direct size-based separation without prior lysis 26,27,45,[63][64][65][66][67][68][69] . Besides the reduction of blood cells of larger or similar diameter than the targeted bacteria and the potential release of phagocytosed but viable bacterial cells 38 , other benefits might arise from selective blood cell lysis as a first step in sample preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Purification of small particles, e.g. bacteria and platelets [25][26][27][28] has been achieved by acoustically pushing away the larger particles from the smaller particles, but this approach does not enable isolation of sub-micron-sized biological particles from a complex background of molecules, particles or debris that are of smaller size, which is essential for purification protocols. Recently sub-micron particles were pushed away from 100-nm-particles by surface acoustic waves 29,30 and the same approach was applied to separate red blood cells and microvesicles from exosomes in a two-stage process 31 .We recently found that, for bulk acoustic waves, acoustic streaming can be greatly reduced by introducing a gradient in acoustic impedance (mass density times speed of sound) in the acoustic cavity by standard gradient centrifugation media 32,33 .…”
mentioning
confidence: 99%
“…Successful techniques for bacterial separation from blood include microfluidics [17][18][19] and capture on magnetic beads. [20][21][22][23] These techniques have been reviewed recently 24 and are summarized in Table S2.…”
Section: Background Of Separation By Sedimentationmentioning
confidence: 99%
“…The device was capable of identifying not only the internal structure of the bacteria such as Gram positive or negative but also measuring the size of individual bacteria at the same time. Very recently, two microfluidic platforms have been proposed for isolation of bacteria from blood cells at high cell concentrations employing acoustophoresis in a silicon (Ohlsson et al 2018) and plastic microfluidic chips (Dow et al 2018) at a sample flow rate of 50-400 μL/min which leads to high enough throughput for many clinical applications (Cetin et al 2014). However, both platforms rely on bulky hardware for flow control and acoustic actuation, and lack of a rapid detection systems.…”
Section: Introductionmentioning
confidence: 99%